2013
DOI: 10.3109/14767058.2013.776533
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and laboratory findings in early- and late-onset preeclampsia

Abstract: The results confirmed the opinion that EOP is a distinct and more severe clinical entity than LOP. In particular, higher proteinuria is associated with EOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 26 publications
0
24
0
4
Order By: Relevance
“…We found that early onset maternal preeclampsia was associated with higher risk of childhood asthma. Early onset preeclampsia may have different etiology and clinical manifestations than late onset preeclampsia . A study has shown that early, but not late onset preeclamptic placentae lose their ability to properly respond to variations in oxygen tension .…”
Section: Discussionmentioning
confidence: 99%
“…We found that early onset maternal preeclampsia was associated with higher risk of childhood asthma. Early onset preeclampsia may have different etiology and clinical manifestations than late onset preeclampsia . A study has shown that early, but not late onset preeclamptic placentae lose their ability to properly respond to variations in oxygen tension .…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with those of studies showing that neonates born to mothers with early‐onset preeclampsia have lower birth weights, more often requiring admission to the NICU and oxygen supplementation, as well as having longer NICU stays. Therefore, preeclampsia has a profound effect of neonates, who are subject to the adverse effects of prematurity, low birth weight, and respiratory distress …”
Section: Discussionmentioning
confidence: 99%
“…At later gestations (>20 weeks), angiogenic factors have been reported to perform better for detection of early‐onset (< 34 weeks) than late‐onset PE (≥34 weeks) . This has been attributed to a greater severity of early‐onset cases, or, as suggested by some, that late onset PE might be a different subtype . We have suggested an alternative explanation, namely that at term syncytiotrophoblast stress is increasing in all pregnancies, (accompanied by increasing stillbirth and pre‐eclampsia rates), that all women would get pre‐eclampsia if spontaneous delivery did not intervene, so that the background of normality allowing clear diagnosis simply does not exist.…”
Section: Prediction Of Diseasementioning
confidence: 94%